Patient Characteristics and Primary Care Enrolment: The Case of Australia's MyMedicare - Ron Fisher; Ou Yang; Susan J. Méndez; Jongsay Yong; Yuting Zhang; Crystal McPhee; Hannah Lack; Karinna Saxby (Australian Economic Review, 2026)
ABSTRACT Research Question/Issue This study examines the patient characteristics associated with enrolment in MyMedicare, Australia's first national voluntary primary care enrolment program, introduced in October 2023. Research Findings/Insights Enrolment is positively associated with each of the eight chronic condition groups examined, although the magnitude of association varies across conditions. Enrolment is also increasingly likely with greater multimorbidity. Females, older adults, patients living in relatively socioeconomically advantaged areas and those with greater pre‐policy primary care use are also more likely to enrol. Practitioner/Policy Implications MyMedicare enrolment appears broadly aligned with clinical need, with greater uptake among patients with chronic conditions and particularly those with multimorbidity. However, enrolment is also more common among patients with stronger existing engagement with primary care. As additional benefits and service entitlements become linked to MyMedicare, policymakers should monitor whether patients with weaker existing primary care engagement are being reached. Methods used We analyse linked electronic health records from more than 1.3 million patients across 350 general practices using multivariable logistic regression models. The analysis examines associations between MyMedicare enrolment and clinical, sociodemographic and pre‐policy healthcare use characteristics.